Effect of aqueous extract of spondias mombin on the spermiogram of wistar rats (2011)
Twenty-five male rats were divided into four groups (A-E) and treated for twenty-one days with aqueous leaf extract of Spondias mombin which is a fruit tree whose leaf extract is commonly consumed as local remedies in traditional medicine practice. Graded dosages of the extracts were assigned to the groups as follows: 200mg/kg, 400 mg/kg, 600 mg/kg and 800 mg/kg for groups B, C, D and E, respectively. Group A rats which serve as control were given distilled water. Thereafter, spermiogram (mass activity, progress motility, live-dead and morphology) was evaluated. Rats treated with aqueous extracts of spondias mombin at 600 mg/kg body weight has the highest (p<0.05) spermatozoa concentration of 40.51x106 cells/ml. compared with other groups A, B, C and E which had 21.48 x 106, 29.58 x 106, 35.81 x 106/ml, respectively. At dosage of 800 mg/kg highest (p<0.05) sperm motility of 70 ± 4.81% was observed. Compared with other groups A, B, C and D which had 65.0 ± 0.00, 65.5 ± 6.71 and 68.0 ± 2.89%, respectively. The percentage average livability of the control group and of those given 200 mg/kg BW, 70 ± 23.45 and 70 ± 23.09, respectively, were lower than those from group C (77.5 ± 15.55), D (87.5 ± 17.68) and E (80.0 ± 17.32) with group D having the highest average percentage livability. Coiled tail was the predominant abnormality in group A, B and E consisting 40.3%, 24.3% and 30.0% of the total abnormalities, respectively. The work recommended aqueous extract of spondias mombin at concentration of 600mg/ml for of fertility enhancement in male animals.